The Secrets of Classical Arabic: Perspectives on the Science of Language - Riyadi, Achmad Ilham; Kurniawan, Agus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Classical Arabic, which began to develop in the 7th century CE, played a crucial role in laying the foundations of linguistic science (‘ilm al-lughah) within the Islamic intellectual tradition. During this period, several prominent scholars emerged who not only pioneered the study of grammar but also established methodological principles that remain relevant in modern linguistic research. Scholars such as Sibawayh, Al-Khalil ibn Ahmad, and Al-Farahidi made significant contributions to the development of key linguistic concepts, including morphology (ṣarf), syntax (naḥw), and phonology (ṣawt). Their ideas reflect an approach to language that was not merely normative or descriptive, but also analytical and contextual. The science of language in the classical Arabic tradition addressed not only formal grammatical rules but also pragmatic and sociolinguistic dimensions, especially concerning eloquent and contextually appropriate language use. Monumental works such as Al-Kitāb by Sibawayh and Kitāb al-‘Ayn by Al-Farahidi remain intellectual legacies that continue to be studied in contemporary Arabic linguistics. This study aims to review classical perspectives on language within the framework of ‘ilm al-lughah, and to explore their enduring impact on the understanding and teaching of Arabic in the modern era.